Effect of whole-body vibration warm-up on bat speed in women softball players - Dabbs, N. C.; Brown, L. E.; Coburn, J. W.; Lynn, S. K.; Biagini, M. S.; Tran, T. T. (The Journal of Strength and Conditioning Research, 2010)
Whole-body vibration (WBV) may enhance human performance via augmented muscular strength and motor function if used before performance. Because warm-up is a crucial aspect of preparation for performance, it remains unknown if WBV may enhance bat speed. The purpose of this study was to investigate the effect of WBV warm-up on bat speed. Eleven National Collegiate Athletic Association division I and 11 recreationally trained female softball players volunteered to participate. Subjects randomly performed 3 different warm-up conditions consisting of WBV alone, dry swings alone (DS), and WBV with dry swings (WBVDS). Whole-body vibration was performed on a pivotal vibration platform at a frequency of 25 Hz and an amplitude of 13 mm for one 30-second bout. Thirty seconds after each warm-up condition, 5 maximal bat swings were recorded. There was no significant (p > 0.05) difference between groups by training status, and there was no significant (p > 0.05) difference between WBV (42.39 ± 9.83 mph), DS (40.45 ± 11.00 mph), or WBVDS (37.98 ± 12.40 mph) conditions. These results indicate that WBV warm-up may be used in place of DS to achieve similar bat speeds. Future research should investigate different combinations of WBV warm-up using various frequencies, durations, amplitudes, and rest times.